Complex Study of Settlements Dating from the Paleolithic to Medieval Period in the Ural Mountains on the Border of Europe and Asia - Valentina Prikhodko; Nikita Savelev; Vyacheslav Kotov; Sergey Nikolaev; Evgeny Ruslanov; Mikhail Rumyantsev; Elena Manakhova (Geosciences)
Soil, geochemical, microbiological, and archeological studies were conducted at eight settlements dating from the Paleolithic to Late Medieval and Modern Ages near the southern Trans-Urals Mountains, Russia. The forest-steppe landscapes, rivers, and abundant mineral resources have attracted people to the region since ancient times. Cultural layers (CLs) are marked by finds of ceramics fragments, animal bones, stone, and metal tools. The properties of CLs include close-to-neutral pH, being well structured, the absence of salinity, enrichment with exchangeable calcium, and anthropogenic phosphorus (0.2–0.4%). The majority of CLs start at a depth of 3–25 cm, extend to 40–60 cm, and contain 6–10% organic carbon (Corg) in the 0–20 cm layer, reflecting carbon input from modern-day processes. At the Ishkulovo site (0.6–0.8 ka BP), Corg decreases to 1.3% because the CL is below 80 cm, and in the absence of fresh organic material input, carbon has been mineralized. The proximity of sites to deposits of copper, chromium, zinc, and manganese in the Ural Mountains creates natural high-content anomalies in the region, as indicated by their abundance in soils and parent rocks. In the past, these elements were also released into CLs from metal products, ceramic fragments, and raw materials used in their manufacture. The sites are quite far (18–60 km) from the Magnitogorsk Metallurgical plant, but industrial stockpiles of S (technogenic coefficient—Ct 30–87%), and, less often, Cr, Mn, and Sr (Ct 30–40%) accumulated in surface layers. These three factors have led to the concentration of pollutants of the first (arsenic, chromium, lead, and zinc) and second (cobalt, copper, and nickel) hazard classes at CLs, often in quantities 2–5 times higher than values for parent materials and geosphere average content (“Clarke” value), and, and less often, more than the allowable content for human health. This may have influenced their health and behavioral functions. Due to the above properties, chernozems have a high buffering capacity and a strong bond with heavy metals. Therefore, no inhibition of microbes was observed. The microbial biomass of the 0–10 cm layer is high, 520–680 µg C/g, and microbes cause the emission of 1.0 C-CO2 µg/g of soil per hour. During the ancient settlements’ development, a favorable paleoclimate was noted based on the data cited. This contributed to the spread of productive paleolandscapes, ensuring the development of domestic cattle breeding and agriculture.